Ascorbic acid as a modulator of inflammatory response against Candida albicans - Moreira Milhan, Noala Vicensoto [UNESP]; Graça Sampaio, Aline da [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Bruzzaniti, Angela (Taylor & Francis, 2024)
Aim: To evaluate the behavior of oral keratinocytes in the presence of Vitamin C (Vit C) and its anti-inflammatory potential. Materials & methods: Oral keratinocytes were initially exposed to 0.1–2.5 mM of Vit C and the metabolic activity and cell migration were evaluated using MTS assay and Ibidi culture inserts, respectively. After, the cells were challenged with Candida albicans and inflammatory markers were analyzed by qPCR. Results: The treatment was not cytotoxic, and the highest concentrations increased the metabolic activity at 24 h. Vit C delayed the cell migration at 48 and 72 h. Interestingly, it downregulated the genes IL-8 and IL-1β. Conclusion: Vit C could be an interesting adjuvant to anti-fungal treatment due to its anti-inflammatory potential.
Keywords: anti-inflammatory; ascorbic acid; candidiasis; infection model; vitamin C